Catalyst slurry for fuel cell and method for preparing catalyst slurry
By using ionomers of different equivalent weights in the fuel cell electrode catalyst layer to form microporous and mesoporous structures, combined with water electrolytic catalysts, the problems of water discharge and carbon corrosion durability are solved, and the excellent performance and interface of the electrode are maximized. .
Patent Information
- Application Number
- CN202010971218.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-26
- Filing Date
- 2020-09-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-09-16
AI Technical Summary
现有技术难以在各种驱动条件下确保燃料电池电极催化剂层的水排放特性和碳腐蚀耐久性,尤其是在离子交换基团数量和氢离子传导率之间找到平衡。
The catalyst particles with two ionomers with different equivalent weights are formed into microporous and mesoporous structures, the first ionomer is on the outer surface and the second ionomer is on the inner surface of the mesoporous, combined with a water electrolytic catalyst to optimize water discharge and Hydrogen ion conduction.
The 3-phase interface in the electrode is maximized, the water discharge characteristics and carbon corrosion durability are improved, and excellent performance under different driving conditions is achieved.
Smart Images

Figure CN112952122B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a catalyst slurry for a fuel cell and a method for preparing the catalyst slurry. Background Art
[0002] For polymer electrolyte membrane fuel cells for vehicles, there is a need for a design technology for electrode catalyst layers that can ensure optimal performance under various driving conditions (temperature / humidity), and in particular, can appropriately discharge water generated during driving of the fuel cell to prevent flooding.
[0003] The ionomer included in the cathode catalyst layer is used to transport protons that react with oxygen to generate electricity. As the equivalent weight (EW) of the ionomer decreases, the number of ion exchange groups increases, and the hydrogen ion conductivity increases, but the discharge of the generated water becomes worse. As the equivalent weight (EW) of the ionomer increases, the hydrogen ion conductivity decreases, but the water discharge characteristics become stronger.
[0004] In order to compensate for the weak points and maximize the strong points according to the equivalent weight (EW) of the ionomer, various techniques and inventions have been developed that can use different kinds of ionomers with different equivalent weights (EW). However, in these cases, the different kinds of ionomers are simply mixed or prepared as separate layers, which has limited effects and is restricted. Summary of the invention
[0005] The present disclosure is directed to solving the above-mentioned problems associated with the prior art, and an object of the present disclosure is to provide a catalyst slurry and a method for preparing the catalyst slurry, which combine the advantages of two ionomers having different equivalent weights (EW) to maximize the 3-phase interface in the electrode and improve the discharge characteristics of the generated water and the carbon corrosion durability.
[0006] In one aspect, the present disclosure provides a catalyst slurry for a fuel cell, the catalyst slurry comprising: an electrode catalyst formed of catalyst particles comprising micropores; and an ionomer layer formed on the electrode catalyst, wherein the electrode catalyst comprises an outer surface and mesopores formed to be recessed from the outer surface to the inside by a predetermined depth, the ionomer layer comprising a first ionomer formed on the outer surface where the micropores of the electrode catalyst are located and a second ionomer formed on the inner surface of the mesopores, and the average length of the side chains of the second ionomer is longer than the average length of the side chains of the first ionomer.
[0007] In a preferred embodiment, the catalyst particles may include a support body loaded with a catalyst metal.
[0008] In another preferred embodiment, the catalyst metal may include one selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni) and combinations thereof.
[0009] In another preferred embodiment, the support may include one selected from the group consisting of carbon black, acetylene black, Ketjenblack, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires, and combinations thereof.
[0010] In yet another preferred embodiment, the support may include micropores with a size less than 2 nm.
[0011] In another preferred embodiment, the particle diameter of the catalyst particles may be less than 1 μm.
[0012] In another preferred embodiment, the mesopores may be open from the inside to the outside of the electrode catalyst and include a pore entrance connected to the outer surface of the electrode catalyst, the diameter of the pore entrance may be 2nm to 50nm, and the depth of the mesopores may be 2nm to 200nm.
[0013] In yet another preferred embodiment, the first ionomer may have an equivalent weight (EW) of 400 to 800, and include one selected from the group consisting of polysulfone-based resin, polyether ketone-based resin, polyether-based resin, polyester-based resin, polybenzimidazole-based resin, polyimide-based resin, and combinations thereof.
[0014] In yet another preferred embodiment, the second ionomer may have an equivalent weight (EW) of 800 to 1200 and include one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.
[0015] In yet another preferred embodiment, the second ionomer may be formed on the outer surface of the electrode catalyst where the micropores are located.
[0016] In another preferred embodiment, the electrode catalyst may further include: a water electrolysis catalyst, loaded on the inner surface of the mesopore, the water electrolysis catalyst may be mixed with the second ionomer, and the water electrolysis catalyst may include a metal catalyst or an oxide thereof selected from the group consisting of iridium (Ir), ruthenium (Ru), and combinations thereof.
[0017] In yet another preferred embodiment, the loading amount of the water electrolysis catalyst loaded on the inner surface of the mesopores may be 10 parts by weight to 50 parts by weight based on 100 parts by weight of the electrode catalyst.
[0018] In another aspect, the present disclosure provides a method for preparing the above-mentioned catalyst slurry for a fuel cell, the method comprising: preparing a starting material comprising catalyst particles, a first ionomer and a pore former; obtaining an intermediate product comprising a composite of catalyst particles and a pore former, the outer surface of which is coated with the first ionomer by heat-treating the starting material; obtaining an electrode catalyst having mesopores by removing the pore former from the intermediate product; and coating a water electrolysis catalyst and a second ionomer on the inner surface of the mesopores.
[0019] In a preferred embodiment, the pore former may include silicon dioxide having a particle diameter of 5 nm to 50 nm.
[0020] In another preferred embodiment, based on 100 parts by weight of the catalyst particles, the content of the pore former may be 10 parts by weight to 50 parts by weight.
[0021] In yet another preferred embodiment, the starting material may include 60 wt % to 80 wt % of the catalyst particles and the pore former and 20 wt % to 40 wt % of the first ionomer.
[0022] In yet another preferred embodiment, the starting material may be prepared by dispersing the catalyst particles and the pore former in a solvent and then dispersing the first ionomer in the resultant.
[0023] In yet another preferred embodiment, the intermediate product may be obtained by heat-treating the starting material at a temperature of 100° C. to 140° C. for 2 to 4 hours.
[0024] In another preferred embodiment, the pore former can be removed by placing the intermediate product into an alkaline solution and then refluxing.
[0025] In yet another preferred embodiment, the electrode catalyst, the water electrolysis catalyst, and the second ionomer may be dispersed in a solvent to coat the second ionomer on the inner surface of the mesopores.
[0026] Other aspects and preferred embodiments of the disclosure are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The above and other features of the present disclosure will now be described in detail with reference to some exemplary embodiments of the present disclosure shown in the accompanying drawings, which are given below by way of illustration only and therefore do not limit the present disclosure, wherein:
[0028] Figure 1 is a view schematically showing a conventional electrode catalyst slurry;
[0029] Figure 2 is a view showing a catalyst slurry for a fuel cell according to the present disclosure;
[0030] Figure 3 It is shown Figure 2 A view of a catalyst particle;
[0031] Figure 4 It is shown by Figure 3 A view of an electrode catalyst formed by agglomeration of catalyst particles is shown;
[0032] Figure 5 is a flow chart showing a method for preparing a catalyst slurry according to the present disclosure;
[0033] Figure 6 is a diagram showing an intermediate product formed during the above method; and
[0034] Figure 7 is a reference view showing the formation of mesopores by removing a pore former from an intermediate product.
[0035] It should be understood that the accompanying drawings are not necessarily drawn to scale, presenting a somewhat simplified representation of various preferred features illustrating the basic principles of the present disclosure. The specific design features of the present disclosure as disclosed herein, including, for example, specific dimensions, directions, locations, and shapes, will be determined in part by specific intended applications and use environments.
[0036] In the drawings, reference numerals refer to the same or equivalent parts of the present disclosure throughout the several figures of the drawing. DETAILED DESCRIPTION
[0037] Hereinafter, reference will be made to various embodiments of the present disclosure in detail. Examples of various embodiments of the present disclosure are shown in the accompanying drawings and described below. Although the present disclosure will be described in conjunction with the exemplary embodiments, it will be understood that this specification is not intended to limit the present disclosure to the exemplary embodiments. On the contrary, the present disclosure is intended to cover not only the exemplary embodiments, but also various alternatives, modifications, equivalents and other embodiments within the scope and spirit of the present disclosure as defined by the appended claims.
[0038] In the following description of the embodiments, the same elements are represented by the same reference numerals even if they are depicted in different drawings. In the accompanying drawings, for clarity of explanation, the size of the structure is exaggerated compared to the actual size of the structure. In the following description of the embodiments, various elements may be described using terms such as "first", "second", etc., but these terms do not limit these elements. These terms are only used to distinguish an element from other elements. For example, within the thought and scope of the present disclosure, the first element may be named as the second element, and similarly, the second element may be named as the first element. The singular may contain the plural unless there is a significantly different contextual meaning.
[0039] In the following description of the embodiments, terms such as "including", "having", etc. will be interpreted as indicating the presence of features, numbers, steps, operations, elements, components, or combinations thereof described in the specification, and do not exclude the presence of one or more other features, numbers, steps, operations, elements, components, or combinations thereof, or the possibility of adding one or more other features, numbers, steps, operations, elements, components, or combinations thereof. In addition, it will be understood that when a component such as a layer, film, region, or plate is referred to as "above another component", the component may be "directly above the other component", or other components may be inserted between the two components. In the same way, it will be understood that when a component such as a layer, film, region, or plate is referred to as "below another component", the component may be "directly below the other component", or other components may be inserted between the two components.
[0040] All numbers, values and / or expressions used in the specification to indicate the number of components, reaction conditions, polymer compositions and mixtures are approximate values that reflect the various measurement uncertainties that arise when these values are obtained from essentially different things. Therefore, it will be understood that all numbers, values and / or expressions indicating the number of components, reaction conditions, polymer compositions and mixtures are modified by the term "about" unless otherwise stated. In addition, it will be understood that if a numerical range is disclosed in the specification, the range includes all continuous values from the minimum value to the maximum value of the range, unless otherwise stated. In addition, if the range refers to an integer, the range includes all integers from the minimum integer to the maximum integer, unless otherwise stated.
[0041] The ionomer used in the fuel cell is used to transport hydrogen ions in the electrode. Since the properties of the ionomer change according to its equivalent weight (EW), it is important to use which ionomer to form the electrode. Specifically, when the equivalent weight (EW) of the ionomer is low, the number of ion exchange groups is large, and the hydrogen ion conductivity increases, but the ionomer has a high hydrophilicity and cannot discharge water smoothly. On the other hand, when the equivalent weight (EW) of the ionomer is high, the hydrogen ion conductivity is low, but the ionomer has a high hydrophobicity and can discharge water smoothly. Therefore, a technology for forming an electrode using two ionomers with different equivalent weights (EW) is proposed.
[0042] Figure 1 Schematically showing a conventional electrode catalyst slurry. Specifically, an ionomer 70 having a low equivalent weight (EW) and an ionomer 80 having a high equivalent weight (EW) are mixed, and then the obtained mixture is coated on an electrode catalyst 90. However, in this case, the ionomer 70 and the ionomer 80 are randomly adhered to the surface of the electrode catalyst 90, so the effect that can be obtained is limited.
[0043] In the present disclosure, in order to overcome the conventional limitations, two ionomers having different equivalent weights (EW) are used, but the ionomers may be respectively formed at positions suitable for maximizing their functions.
[0044] Figure 2 is a view showing a catalyst slurry for a fuel cell according to the present disclosure. Figure 2 The catalyst slurry includes: an electrode catalyst 10 formed by agglomerating catalyst particles 11 ; and an ionomer layer 20 formed on the electrode catalyst 10 .
[0045] Figure 3 is a view showing the catalyst particles 11. Figure 3 The catalyst particles 11 may include a support 112 carrying a catalyst metal 111 .
[0046] The catalyst metal 111 may include one selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni), and combinations thereof.
[0047] The support 112 may include one selected from the group consisting of carbon black, acetylene black, Ketjen black, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires, and combinations thereof.
[0048] The support body 112 may include micropores 112a having a size less than 2 nm.
[0049] The catalyst particles 11 are not limited to any specific diameter, for example, the diameter of the catalyst particles 11 may be 1 μm or less. Here, the diameter of the catalyst particles 11 may refer to the distance from one point on the surface of the catalyst particles 11 to another point on the surface of the catalyst particles 11 opposite to the point. When the diameter of the catalyst particles 11 exceeds 1 μm, the mesopores 12 of the electrode catalyst 10 may not be smoothly formed, which will be described below.
[0050] Figure 4 1 is a view showing an electrode catalyst 10 formed by agglomeration of catalyst particles 11 .
[0051] The electrode catalyst 10 may include an outer surface and mesopores 12 that are recessed from the outer surface to the inside by a predetermined depth.
[0052] The mesopores 12 are not limited to any particular shape, and may have, for example, a channel shape whose cross section is elongated from the outer surface toward the inside of the electrode catalyst 10 , or a nearly hemispherical shape.
[0053] Specifically, the mesopore 12 may be open from the inside to the outside of the electrode catalyst 10 and include a pore entrance connected to the outer surface of the electrode catalyst 10 , the diameter of the pore entrance may be 2 nm to 50 nm, and the depth of the mesopore 12 may be 2 nm to 200 nm.
[0054] The mesopores 12 serve as channels for discharging water generated during operation of the fuel cell. Therefore, ionomers that facilitate water discharge are preferably located in the mesopores 12. On the other hand, micropores 112a generated by the catalyst particles 11, more precisely, by the support 112, are located on the outer surface of the electrode catalyst 10. The catalyst metal 111 is supported on the micropores 112a, and therefore, ionomers that have excellent hydrogen ion conductivity rather than water discharge can be located around the micropores 112a.
[0055] Based on this, in this disclosure, Figure 2 As shown, the first ionomer 21 having a short average side chain length, low equivalent weight (EW) and high hydrogen ion conductivity is configured to contact the outer surface of the electrode catalyst 10, and the second ionomer 22 having a long average side chain length, high equivalent weight (EW) and smoothly discharging water is configured to contact the inner surface of the mesopore 12.
[0056] In more detail, the first ionomer 21 may have an equivalent weight (EW) of 400 to 800 and include one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof. The first ionomer 21 has a short average length of side chains, so it can smoothly contact the catalyst metal 111 loaded on the micropores 112a, and has high hydrogen ion conductivity. However, the first ionomer 21 has high hydrophilicity, so it is not conducive to water discharge.
[0057] The second ionomer 22 may have an equivalent weight (EW) of 800 to 1200 and include one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof. The second ionomer 22 has a long side chain and is therefore hydrophobic, which is beneficial for water discharge. However, the contact between the second ionomer 22 and the catalyst metal 111 supported on the micropores 112a is greatly reduced.
[0058] The electrode catalyst 10 may further include a water electrolysis catalyst 13 supported on the inner surface of the mesopore 12. As described above, the mesopore 12 serves as a water discharge channel, but the support 112 is corroded by moisture. The present disclosure aims to prevent this problem by applying the water electrolysis catalyst 13 to the inner surface of the mesopore 12.
[0059] The water electrolysis catalyst 13 is not limited to any specific substance, and for example, may include one metal catalyst selected from the group consisting of iridium (Ir), ruthenium (Ru), and a combination thereof, or an oxide thereof.
[0060] The loading amount of the water electrolysis catalyst 13 supported on the inner surface of the mesopores 12 may be 10 parts by weight to 50 parts by weight based on 100 parts by weight of the electrode catalyst 10 .
[0061] Figure 5 1 is a flow chart showing a method for preparing a catalyst slurry according to the present disclosure, which may include: preparing a starting material including catalyst particles, a first ionomer and a pore former (S10); obtaining an intermediate product including a composite of catalyst particles and a pore former whose outer surface is coated with the first ionomer by heat-treating the starting material (S20); obtaining an electrode catalyst having mesopores by removing the pore former from the intermediate product (S30); and coating a second ionomer on the inner surface of the mesopores (S40).
[0062] The method is characterized in that mesopores are formed in the above-mentioned electrode catalyst, and in the process, ionomers are appropriately supplied so that the ionomers can be formed at desired positions, respectively. Hereinafter, the method will be described in more detail.
[0063] Figure 6 2 is a diagram showing an intermediate product. The intermediate product may be obtained by heat-treating a starting material including the catalyst particles 11 , the first ionomer 21 , and the pore former 30 .
[0064] The pore former 30 may include silicon dioxide having a particle diameter of 5 nm to 50 nm. When the particle diameter of the pore former 30 is less than 5 nm, the size of the mesopores to be formed is too small, so it is difficult to remove the pore former 30. On the other hand, when the particle diameter of the pore former 30 exceeds 50 nm, the size of the mesopores is too large, so the number of mesopores is reduced and the specific surface area of the electrode catalyst is reduced.
[0065] The content of the pore former 30 is not limited to any specific value. For example, based on 100 parts by weight of the catalyst particles 11 , the content of the pore former 30 may be 10 parts by weight to 50 parts by weight.
[0066] In addition, the starting material may include 60 to 80 wt % of the catalyst particles 11 and the pore former 30 and 20 to 40 wt % of the first ionomer 21. When the respective components are included within the above content ranges, mesopores having an appropriate size may be formed in an appropriate ratio.
[0067] In addition, the starting material may be prepared by dispersing the catalyst particles 11 and the pore former 30 in a solvent and then dispersing the first ionomer 21 in the resultant. Figure 6 As shown, this is to coat the first ionomer 21 on the outer surface of the composite including the catalyst particles 11 and the pore former 30 rather than the inside of the composite.
[0068] The solvent is not limited to any specific substance, and, for example, may include one selected from the group consisting of distilled water, ethanol, propanol, and combinations thereof.
[0069] The method may further include drying the starting material before heat-treating the starting material. Specifically, the starting material may be dried at a temperature of 60° C. to 90° C. for more than 12 hours using a drying machine such as an oven. When the drying temperature is too low, the solvent cannot be fully dried, and when the drying temperature is too high, the drying speed is too fast, so the catalyst may catch fire.
[0070] Thereafter, the intermediate product can be obtained by heat-treating the starting material at a temperature of 100° C. to 140° C. for 2 to 4 hours. When the heat treatment temperature is lower than 100° C., the heat treatment temperature is lower than the glass transition temperature Tg of the first ionomer 21, so the first ionomer 21 cannot be properly fixed to the surface of the metal catalyst, and when the heat treatment temperature is higher than 140° C., the structure of the ionomer and the catalyst is collapsed due to overheating.
[0071] Afterwards, if Figure 7 As shown, mesopores 12 may be formed by removing pore former 30 from the intermediate product ( S30 ).
[0072] Specifically, the intermediate product may be placed in an alkaline solution and then refluxed to remove the pore former 30. At this time, the pore former 30 and the first ionomer 21 coated on the surface of the pore former are removed simultaneously.
[0073] The alkaline solution can be obtained by dissolving a hydroxide of an alkali metal or an alkaline earth metal in distilled water. Here, the alkaline solution having an appropriate molar concentration can be prepared so as to sufficiently dissolve the pore former 30. If granular silica is used as the pore former 30, the molar concentration of the alkaline solution is preferably in the range of about 3M to 10M.
[0074] For example, without particular limitation, the reflux condition may be to reflux the alkaline solution into which the intermediate product is placed at a temperature of 50° C. to 95° C. for 2 to 5 hours.
[0075] The electrode catalyst having the mesopores 12 can be obtained by washing and drying the result obtained by the above operation. Figure 7 As shown, the first ionomer 21 is coated on the outer surface of the electrode catalyst.
[0076] After that, Figure 2 The catalyst slurry according to the present disclosure shown may be obtained by coating the second ionomer 22 on the inner surface of the mesopores 12 of the electrode catalyst.
[0077] Specifically, the second ionomer 22 may be coated on the inner surface of the mesopore 12 by dispersing the electrode catalyst and the second ionomer 22 in a solvent.
[0078] The solvent is not limited to any specific substance, and, for example, may include one selected from the group consisting of distilled water, ethanol, propanol, and combinations thereof.
[0079] At this time, the water electrolysis catalyst 13 may be placed in a solvent so that the water electrolysis catalyst 13 is supported on the mesopores 12 .
[0080] The catalyst slurry according to the present disclosure can be used to manufacture an electrode for a fuel cell. The manufacturing method of the electrode is not limited to any specific method, and the electrode can be obtained by coating the catalyst slurry on a substrate material such as a release paper or an electrolyte membrane using various methods such as spraying, bar coating, slot die coating, etc.
[0081] As is apparent from the above description, the catalyst slurry according to the present disclosure may have excellent ability to discharge generated water and excellent carbon corrosion durability.
[0082] Using a catalyst slurry according to the present disclosure can maximize the 3-phase interface in the electrode.
[0083] The present disclosure has been described in detail with reference to the preferred embodiments of the present disclosure. However, it will be appreciated by those skilled in the art that these embodiments may be modified without departing from the principles and ideas of the present disclosure, the scope of which is defined in the appended claims and their equivalents.
Claims
1. A catalyst slurry for a fuel cell, include: an electrode catalyst formed of catalyst particles including micropores; as well as an ionomer layer formed on the electrode catalyst, The electrode catalyst includes an outer surface and a mesopore formed to be recessed from the outer surface to an inner portion by a predetermined depth, The ionomer layer includes a first ionomer formed only on an outer surface of the electrode catalyst where the micropores are located and not formed on an inner surface of the mesopores and a second ionomer formed on the inner surface of the mesopores, and The average length of side chains of the second ionomer is longer than the average length of side chains of the first ionomer.
2. The catalyst slurry for a fuel cell according to claim 1, in, The catalyst particles include a support body loaded with a catalyst metal.
3. The catalyst slurry for a fuel cell according to claim 2, in, The catalyst metal includes one selected from the group consisting of platinum (Pt), palladium (Pd), iridium (Ir), rhodium (Rh), gold (Au), silver (Ag), cobalt (Co), nickel (Ni) and combinations thereof, and the support includes one selected from the group consisting of carbon black, acetylene black, Ketjen black, activated carbon, carbon nanotubes, carbon nanofibers, carbon nanowires and combinations thereof.
4. The catalyst slurry for a fuel cell according to claim 2, in, The support body includes the micropores having a size of less than 2 nm, and the catalyst particles have a particle diameter of 1 μm or less.
5. The catalyst slurry for a fuel cell according to claim 1, in, The mesopore opens from the inside of the electrode catalyst to the outside and includes a pore entrance connected to the outer surface of the electrode catalyst, the pore entrance has a diameter of 2 nm to 50 nm, and the mesopore has a depth of 2 nm to 200 nm.
6. The catalyst slurry for a fuel cell according to claim 1, in, The first ionomer has an equivalent weight (EW) of 400 to 800 and includes one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof, and the second ionomer has an equivalent weight (EW) of 800 to 1200 and includes one selected from the group consisting of polysulfone-based resins, polyetherketone-based resins, polyether-based resins, polyester-based resins, polybenzimidazole-based resins, polyimide-based resins, and combinations thereof.
7. The catalyst slurry for a fuel cell according to claim 1, in, The second ionomer is formed on the outer surface of the electrode catalyst where the micropores are located.
8. The catalyst slurry for a fuel cell according to claim 1, in, The electrode catalyst further comprises: A water electrolysis catalyst is supported on the inner surface of the mesopores, The water electrolysis catalyst is mixed with the second ionomer, and the water electrolysis catalyst includes one metal catalyst selected from the group consisting of iridium (Ir), ruthenium (Ru), and a combination thereof, or an oxide thereof.
9. The catalyst slurry for a fuel cell according to claim 8, in, The water electrolysis catalyst supported on the inner surface of the mesopores has an amount of 10 to 50 parts by weight based on 100 parts by weight of the electrode catalyst.
10. A method for preparing the catalyst slurry for a fuel cell according to claim 1, wherein the method include: preparing a starting material including catalyst particles, a first ionomer, and a pore former; Obtaining an intermediate product including a composite of the catalyst particles and the pore former, the outer surface of which is coated with the first ionomer, by heat-treating the starting material; obtaining an electrode catalyst having mesopores by removing the pore former from the intermediate product; as well as A water electrolysis catalyst and a second ionomer are coated on the inner surface of the mesopores.
11. The method according to claim 10, in, The pore former includes silicon dioxide having a particle diameter of 5 nm to 50 nm, the content of the pore former is 10 to 50 parts by weight based on 100 parts by weight of the catalyst particles, and the starting material includes 60 wt % to 80 wt % of the catalyst particles and the pore former and 20 wt % to 40 wt % of the first ionomer.
12. The method according to claim 10, in, The starting material is prepared by dispersing the catalyst particles and the pore former in a solvent and then dispersing the first ionomer in the resultant.
13. The method according to claim 10, in, The intermediate product is obtained by heat-treating the starting material at a temperature of 100° C. to 140° C. for 2 to 4 hours.
14. The method according to claim 10, in, The pore former is removed by placing the intermediate product into an alkaline solution and then refluxing.
15. The method according to claim 10, in, The electrode catalyst, the water electrolysis catalyst, and the second ionomer are dispersed in a solvent to coat the second ionomer on the inner surface of the mesopores.
Citation Information
Patent Citations
Fuel cell and its manufacturing method
JP2004281305A
Electrode for fuel cell
JP2008041411A
Electrode for fuel cell and its manufacturing method
JP2011222192A
Method for manufacturing electrode catalyst layer and solid polymer fuel cell
JP2012043612A
Catalyst layer for fuel cell, electrolyte membrane-electrode assembly and fuel cell
JP2019121521A
